Probabilistic forecasting of solar PV power generation - Du, Ziyao (2019)
The penetration of solar photovoltaic (PV) generation grew fast in recent years based on the situation that the demand for renewable energy increased rapidly. However, because of high intermittency of solar power, the integration of solar PV generation may cause significant challenges to operation and control for power grids. Hence, to predict solar PV generation is a fundamental and important task for power utilities.